Training Mothers of PKK Gintung Village, Sukadiri Sub-District, in Optimizing the Management of Zakat, Infaq, and Sedekah for Local Economic Empowerment - Supitriah; Ibnu Hajar (IRDH International Journal of Social Sciences & Humanities, 2025)
This research and community program was conducted in August 2025 in Gintung Village, Sukadiri Sub-District, Tangerang Regency, with the objective of providing training to PKK members to enhance their understanding and optimize the management of Zakat, Infaq, and Sedekah (ZIS) to foster local economic empowerment. Currently, ZIS is often perceived solely as an individual religious obligation; however, when managed structurally and professionally, ZIS possesses significant potential to improve community welfare, particularly at the village level. Challenges encountered in the field include low public literacy regarding ZIS governance, a lack of transparency in its management, and the absence of utilization strategies oriented towards long-term economic empowerment. Through the seminars, participants gained an understanding of the fundamental principles of Sharia economics, the mechanisms for ZIS collection and distribution, and accountable and equitable management practices. Furthermore, insights were provided on how ZIS funds can be directed toward microenterprise development, skills enhancement for homemakers, and the establishment of community-based Sharia cooperatives. The outcomes of the activity indicate that PKK members demonstrate high enthusiasm and commitment to actively participating in the management of ZIS within their community. This training is expected to foster a village-based ZIS management model that can realize local economic independence, reduce community dependence on external assistance, and strengthen social solidarity.